2022
DOI: 10.3390/plants11243523
|View full text |Cite
|
Sign up to set email alerts
|

Irrigation Effect on Yield, Skin Blemishes, Phellem Formation, and Total Phenolics of Red Potatoes

Abstract: Dark Red Norland is an important potato cultivar in the fresh market due to its attractive bright, red colour, and good yield. However, skin blemishes such as silver patch, surface cracking, and russeting can negatively influence the tuber skin quality and marketability. It is well known that potato is a drought-sensitive plant. This study was conducted to determine whether irrigation would affect Dark Red Norland’s yield and skin quality. A three-year field trial was conducted by Peak of the Market in Manitob… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
0
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 51 publications
0
0
0
Order By: Relevance
“…2022) investigated the benefits of irrigation on Dark Red Norland potatoes known to be drought sensitive. The use of irrigation improved yields by 20.6% and reduced surface cracking by 48.5% [11]. Microscopy imaging analysis demonstrated that tubers from the rainfed trials formed higher numbers of suberized cell layers than those of the irrigated potatoes.…”
Section: The Growth and Biochemical Composition Of Microgreens Grown ...mentioning
confidence: 95%
See 1 more Smart Citation
“…2022) investigated the benefits of irrigation on Dark Red Norland potatoes known to be drought sensitive. The use of irrigation improved yields by 20.6% and reduced surface cracking by 48.5% [11]. Microscopy imaging analysis demonstrated that tubers from the rainfed trials formed higher numbers of suberized cell layers than those of the irrigated potatoes.…”
Section: The Growth and Biochemical Composition Of Microgreens Grown ...mentioning
confidence: 95%
“…In addition, surface cracking and silver patch skins had more suberized cell layers than the normal skins. The irrigated potatoes also had a significantly higher concentration of total polyphenols [11]. 2022) investigated the effect of long-term changes in soil microbial composition and subsequent translation on plant metabolic pathways.…”
Section: The Growth and Biochemical Composition Of Microgreens Grown ...mentioning
confidence: 99%